Developing Hanyut Lancang Local Wisdom-Based Interactive Multimedia to Enhance Student Tolerance - Araida Purba; Reh Bungana Beru Perangin-angin; Hapni Laila Siregar; Surya Dharma; Yakobus Ndona; Yusnadi (International Journal on Integrated Education, 2026)
This study aims to develop viable, practical, and effective interactive learning multimedia based on Hanyut Lancang local wisdom to enhance the tolerance character of fifth-grade students at SD Negeri 132410 Tanjungbalai. Utilizing the 4-D Research and Development (R&D) model comprising Define, Design, Develop, and Disseminate the study yielded several key findings. First, media feasibility validation by material, media, and language experts achieved "Highly Viable" criteria, scoring 89.4%, 91%, and 91.5%, respectively. Second, practicality tests conducted via questionnaires for teachers and 28 students indicated "Highly Practical" responses, averaging 95% and 95.5%. Third, effectiveness analysis using pre and post questionnaires revealed a "Moderately Effective" category, demonstrating an increase in mean scores from 48.00 to 82.68 and an N-Gain score of 68.47%. Furthermore, the independent sample t-test showed a significance value of 0.000 < 0.05, confirming a significant difference in tolerance character between the experimental and control classes. In conclusion, the developed interactive learning multimedia is feasible, practical, and effective for enhancing student tolerance characters during cultural diversity lessons.